Towards interventionist research with theoretical ambition - Lukka Kari; Wouters Marc (Elsevier, 2022)
A distinct strength of interventionist research (IVR) is the ability to establish particularly good access to a research partner organization and collect exceptionally detailed information, which may not be available to researchers who employ other approaches. Yet, a challenge of IVR is to exploit this data-gathering opportunity in full, in order to develop a theoretical contribution. We propose the ‘theoretical focus driven’ mode (TFD mode) as a ‘way of working’ for interventionist research, where the researcher invests extra time up-front to thoughtfully generate and explicate the research questions and theoretical focus. These drive a selective and focused data-gathering effort, as well as the nature of the research intervention. At the same time, the researcher remains inspired by the field work and open to changes in the theoretical focus. Indeed, the TFD mode process tends to be iterative, since it is affected not only by the characteristics of abductive theorising, but also by potentially changing priorities of the target organization, and thereby the initial theoretical focus can become empirically unfeasible. Overall, rather than building on the researcher’s enthusiasm for innovative themes in practice, and casting a broad net for data gathering, the TFD researcher capitalises on the potential of IVR by strengthening the theoretical ambition.